Taming the Puritan: Bibliometric Mapping and Critical Review of the Global Salafism Discourse Trajectory - Lutfi, Muhammad; Ahmad Nur Fuad (Faculty of Ushuluddin and Philosophy, 2025)
This study maps the trajectory of academic discourse on global Salafism (2000–2025) using a mixed-methods approach integrating bibliometric analysis and critical review. Quantitative findings reveal a radical